Building Social Character in Early Childhood through Music and Movement Activities - Prihma Sinta Utami; Luluk Ismayanti; Jaymar M. Cabañeles (International Journal of Learning and Education, 2026)
This study aims to examine the contribution of music and movement activities to improving selfconfidence and expressive abilities in early childhood. A descriptive qualitative method was employed. The research was conducted at KB Kartini Lembahijau in April 2026, involving 23 children aged 4–5 years. Observation, interviews, and documentation served as data collection techniques. The findings reveal that music and movement activities can enhance children's self-confidence, as evidenced by their courage to perform, active participation, and peer interaction. Furthermore, these activities strengthen children's expression through body language, facial changes, and creativity in following musical rhythms. Hence, music and movement can be implemented as an effective learning method to support early childhood social-emotional aspects.